บทบาทของวุฒิสภาตามรัฐธรรมนูญแห่งราชอาณาจักรไทย พุทธศักราช 2540 - ปัทมา สูบกำปัง (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
This research aims at studying and analyzing the role and authority of the senate by the constitution of the Kingdom of Thailand, B.E. 2540 (1997) in pros, cons, and effects about rules and authority of senate that effect the efficiency in action. The research has been done by documentary research. The result of this research shows that senators directly elected by people are mainly responsible for inspection of the Exercise of state Power. However, the result of Political Sociology of Thailand creates the senate or senators into political relationships , namely most senators have relationships with political party or politicians who are in coalition parties or most senators have relationships with political party or politicians who are in the opposition leads 1 which influence whatsoever on the role of the senate. In summary, the source or composition of the senate has a direct influence on how the Senate or senators themselves exert their power and influence as politicians. It does not matter what relationship the senators may have with political parties or politicians in the government or the opposition. These relationships in themselves have no influence whatsoever on the efficiency and effectiveness of their performance as intended by the spirit of the New Constitution.